2014
DOI: 10.1002/jib.138
|View full text |Cite
|
Sign up to set email alerts
|

Application of quantitative nuclear magnetic resonance spectroscopy to biological acidification of barley mashes

Abstract: Spontaneous biological acidification has long been a part of the German brewing tradition, and was historically used to optimize the pH of brewhouse mashes. By facilitating the growth of native barley flora, the production of lactic, acetic and succinic acids sours the mash, functioning in a similar way to the addition of food-grade acids, which are prohibited under the Reinheitsgebot of 1516. Traditionally, sour mashes have been performed at the 'optimum' temperature of 49°C. Quantitative proton nuclear magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several studies were previously reported to identify and quantify the OAs in various food and beverage samples 13 and environmental matrices. 14 Different analytical techniques including Ion exclusion chromatography (IEC), 15 Capillary electrophoresis (CE), 16 Nuclear magnetic resonance (NMR) spectroscopy, 17 High performance liquid chromatography (HPLC), 18 LC-MS, [19][20][21] Gas chromatography-mass spectrometry (GC-MS) 13,22 have been applied for the quantification of OAs from food products. Among all the techniques, the GC-MS technique has certain advantages such as low equipment cost, little solvent requirement, ease of analysis, and data reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were previously reported to identify and quantify the OAs in various food and beverage samples 13 and environmental matrices. 14 Different analytical techniques including Ion exclusion chromatography (IEC), 15 Capillary electrophoresis (CE), 16 Nuclear magnetic resonance (NMR) spectroscopy, 17 High performance liquid chromatography (HPLC), 18 LC-MS, [19][20][21] Gas chromatography-mass spectrometry (GC-MS) 13,22 have been applied for the quantification of OAs from food products. Among all the techniques, the GC-MS technique has certain advantages such as low equipment cost, little solvent requirement, ease of analysis, and data reproducibility.…”
Section: Introductionmentioning
confidence: 99%